(untitled) (SAARC Journal of Agriculture, 2022)
The experiment was conducted under sub-tropical condition during two successive seasons (November-March) of 2017-18 and 2018-19 to investigate the effect of defoliations on morpho- physiological attributes and yield of tomato. The experiment comprised of five levels of defoliation viz., 0 (control), 3, 6, 9 and 12 leaves defoliation from the base out of 17 leaves at the beginning of flowering stage and two widely cultivated varieties viz., TM-110 and TM-135. The plant characters such as leaf area, plant height, number of leaves plant-1, straw weight plant-1, absolute growth rate, number of fruits plant-1, individual fruit weight and fruit yield were not affected up to 6 leaves defoliation irrespective of seasons and genotypes. Interestingly, photosynthesis, nitrate reductase and reproductive efficiency increased with increasing defoliation levels. Morpho-physiological parameters and yield attributes were better in 3 and 6 leaves defoliated plants over the control with being the highest in 6 leaves defoliated plant, which resulting the highest fruit yield. Heavy defoliation not only reduced source sizes but also decreased total sink (fruits) causing lower fruit yields. The lowest morpho-physiological attributes and fruit yield was recorded in 12 leaves defoliated plants. These results indicate that tomato plants can tolerate one-third leaf loss during reproductive stage and the knowledge of which might be essential for maintaining better quality tompato production. SAARC J. Agric., 20(1): 87-96 (2022)